(3fbd ef QSGdI ddLGMX dYGFH Ydjg cJHIs
(3ChdgG (B:s
(3HYO GdHSedI bGd GHh YKeGf YeQh Hf HMQ Hf GdLGMX dYGFH Ydjg cJHI YHJ GdcJGH hfYe GdRNQ hGdZaQ , hfYe GdLdjS hGdMeQ hHYO aeJj QCjJ HSJGfG jMed aj hQhVI JZdH s
(3BNQgG (B:s
(3hbGd Ydi Hf GdLge Cg YTjfj GdfYGS aj ZjQ hbJ fhe hHFS GdTF Gdfhe s
(3Vef eLehY , JQJjHgG (B: 2s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
(3eQcR GdHMK GdYdej (B- (3Ge GdbQj s
Keywords: (3eJaQbGJs